DISKRIMINASI PEREMPUAN BERCADAR DALAM PERSPEKTIF HEGEMONI - Nuryu Wahidah; Ezzah Nuranisah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2020)
This study aims to determine, describe, and explain people's perspectives on veiled women. The existence of community construction that veiled women are labeled as radicals, seen from the many historical phenomena about terrorism always related to women who use the veil. This study aims to look at discrimination against veiled women with a review of historical phenomenology in the study of hegemony. Through this research it can be seen that veiled women are labeled as radicals and terrorists. The understanding of hegemony emphasizes that hegemony will take place if the way of life, way of thinking and views of the people below and governing are influenced by the elite and the mass media. There should be no discrimination against women of any age, religion, ethnicity and status. All must be treated equally, fairly, and do not distinguish between culture, ethnicity, religion and social status. Discrimination in the use of veils in Indonesia which led to a ban on the use of veils on campus which later arose a criticism of the veil ban through the perspective of hegemony theory